Energy Waqf and the Environmental Crisis: Advancing Islamic Philanthropy for Sustainability - Shahmi, Mohammad Aliman; Putra, Muhammad Deni; Fahlefi, Rizal; Arifah, Lidyana; Mansur, Muhammad (Economica: Jurnal Ekonomi Islam, 2025)
This study examines energy waqf as an innovative Islamic philanthropic approach to addressing the growing environmental crisis. Using a literature review methodology, the research explores how religious beliefs, cultural values, and institutional trust influence community acceptance and participation in energy waqf initiatives. The findings reveal that strong religious commitment and cultural norms significantly motivate individuals to engage in such projects, which are widely perceived as acts of environmental stewardship and community service. Additional drivers of participation include emotional and psychological factors, awareness of waqf benefits, and confidence in the credibility of managing institutions. The study highlights the importance of public education and transparent governance in strengthening community involvement and ensuring the sustainability of energy waqf programs. These insights offer valuable guidance for policymakers, religious leaders, and development practitioners aiming to promote climate action through Islamic social finance. Energy waqf emerges not only as a philanthropic tool rooted in Islamic principles but also as a viable strategy for advancing renewable energy adoption and fostering environmentally conscious communities.